2009
DOI: 10.1149/1.3139526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Energy on Pentacene Growth and Characteristics of Organic Thin-Film Transistors

Abstract: Fluorinated hybrid materials were synthesized for a solution-processable gate insulator. The surface energy was modified by perfluoroalkyl chains contained in the hybrid gate insulator itself. We investigated the initial morphology and growth mode of pentacene and the characteristics of organic thin-film transistors ͑OTFTs͒ to determine how these characteristics depend on the surface energy. Pentacene growth was changed from a layer-by-layer mode to a three-dimensional ͑3D͒ island growth mode at low surface en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 13 publications
6
35
0
Order By: Relevance
“…Vollmer et al [40] found that O 2 and water do not react noticeably with pentacene, whereas singlet oxygen/ozone readily oxidizes the organic compound. We deduce that large pentacene grains lead to higher mobility than small grains [41,42]. However, Chou et al [21] found that the grain size did not show any significant relation to μ.…”
Section: Resultsmentioning
confidence: 61%
“…Vollmer et al [40] found that O 2 and water do not react noticeably with pentacene, whereas singlet oxygen/ozone readily oxidizes the organic compound. We deduce that large pentacene grains lead to higher mobility than small grains [41,42]. However, Chou et al [21] found that the grain size did not show any significant relation to μ.…”
Section: Resultsmentioning
confidence: 61%
“…On the other hand, if W ad < 2 γ , the fi lm will grow in small islands (Volmer-Weber Mode) mode. [ 21 ] The growth mode of the thermal evaporated organic molecules would directly affect overall performance of the OFETs especially the carrier mobility. The layer-by-layer growth mode usually results in large and dendritic grains, while the island mode growth can provide a higher packing density in the fi rst few monolayers of organic semiconductors.…”
mentioning
confidence: 99%
“…The layer-by-layer growth mode usually results in large and dendritic grains, while the island mode growth can provide a higher packing density in the fi rst few monolayers of organic semiconductors. [ 22 ] The work adhesion of the DNTT thin fi lm and the BST sample loaded into the evaporation chamber 5 h is evaluated by: [ 21 ] W Figure 2 (e,f) shows the AFM surface morphology of the thermal evaporated DNTT fi lm on BST thin fi lm stored in chamber for 5 h, both island and layer structure can be observed and the average grain size is around 500 nm. In the magnifi ed AFM image in Figure 2 .…”
mentioning
confidence: 99%
“…[14][15][16][17][18] Large pentacene grains have been reported on dielectric surfaces with the total surface energy ranging widely from 25 to 55 mN/m. 14,17 In our experiment, the aliphatic ester-containing PMMA surface, with c total of 37 mN/m and c polar of 6.4 mN/m resulted in large pentacene grains (Fig. 2) and the highest XRD signal intensity (Table I).…”
mentioning
confidence: 99%
“…Of course, the transistor performance is likely to be dominated by the pentacene order very close to the dielectric surface, which may be very different from the bulk and free-surface morphology, as suggested by the "layer þ island" crystal growth mode for the first few layers of pentacene. 16,17,19 In Table I and Fig. 3(a), we present the charge carrier mobility of OTFTs with different dielectric surface buffers and bare TPGDA.…”
mentioning
confidence: 99%